Second primary cancers and recurrence in patients after resection of colorectal cancer: An integrated analysis of trials by Japan Clinical Oncology Group: JCOG1702A. (7th November 2020) - Tanaka, Kiyo; Ogawa, Gakuto; Mizusawa, Junki; Kadota, Tomohiro; Nakamura, Kenichi; Shimada, Yasuhiro; Hamaguchi, Tetsuya; Fujita, Shin; Kitano, Seigo; Inomata, Masafumi; Kanemitsu, Yukihide; Fukuda, Haruhiko; et al.
Abstract: Background: Improvements in early detection and treatment have resulted in an increasing number of long-term survivors of colorectal cancer (CRC). For the survivors, second primary cancer and recurrence are important issues; however, evidence for an appropriate surveillance strategy remains limited. This study aimed to investigate the frequency and timing of second primary cancer in patients after surgery for exploring an appropriate surveillance strategy by using an integrated analysis of three large-scale randomized controlled trials in Japan. Methods: The eligibility criteria of three trials included histologically confirmed CRC and having received surgery. The timing, site and frequency of second primary cancers and recurrence were investigated. Risk factors associated with second primary cancers were also examined. The standardized incidence ratio (SIR) of second primary cancers compared with the national database of the Japan Cancer Registry was estimated. Results: A total of 2824 patients were included in this study. The cumulative incidence of second primary cancer increased over time. The SIR of any second primary cancer was 1.07 (95% CI: 0.94–1.21). The SIR for second primary cancers of colon was 1.09 (95% CI: 0.79–1.47). The cumulative incidence of recurrence almost reached plateau at 3 years. Conclusions: A common surveillance strategy for the general population can be applied even for curatively resected CRC patients, as the risk of second primary cancers was almost the same as that of the general population. Abstract : Our integrated analysis of three large-scale randomized controlled trials in Japan concluded that the Japanese and other countries' guidelines recommending surveillance strategy for resected colorectal cancer patients might be appropriate.